The level of health behavior among second year adolescent students. -Case study at Abdelhamid Ben Badis Secondary School, Guedjel - Daoud, Asma; Seffari, Loubna (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
This study aimed to investigate the level of health behaviour among second-year students enrolled at Abdelhamid Ben Badis Secondary School in Guedjel, as well as to examine differences in health behaviour based on gender and academic stream (scientific vs. literary). The sample comprised 193 students enrolled in the second year at Abdelhamid Ben Badis Secondary School in Guedjel. The students were selected using a simple random sampling method. It comprised 151 female students (78.24%) and 42 male students (21.76%). Among the participants, 113 (58.55%) were enrolled in the scientific stream, while 80 (41.45%) were from the literary stream. The study aimed to investigate the following research questions: -What is the level of health behaviour among second-year adolescents at Abdelhamid Ben Badis Secondary School – Guedjel? -Are there statistically significant differences in health behaviour levels among the participants based on gender or academic stream, at the 0.01 level of significance? To address these research questions, the descriptive method was employed. Besides, the researchers used the Health Behaviour Scale by Al-Samadi (2011), as modified by Al-Harithi (2014), to collect data that had been subjected to statistical analysis. The findings revealed that second year adolescents in the secondary education exhibit a moderate level of health behavior. Additionally, no statistically significant differences in health behavior were found based on gender or academic stream at the 0.01 significance level. Based on these findings, the researchers recommend further exploration of this age group and the adoption of strategies to promote health awareness and educate students on healthy behaviors, given their profound impact on various aspects of an individual's life.